METHOD VALIDATION OF RIFAMPICIN ANALYSIS IN HUMAN PLASMA AND ITS APPLICATION IN BIOEQUIVALENCE STUDY - LUKITANINGSIH, ENDANG; JANNAH, FATHUL; PEBRIANA, RATNA BUDHI; PUSPITA, RATNA DEWI; TAUFIQUROHMAN; IKAWATI, ZULLIES (International Journal of Applied Pharmaceutics, 2019)
Objective: This research aims to validate the method for rifampicin analysis in plasma by using High-Performance Liquid Chromatography (HPLC) that can be used to study the bioequivalence of a generic tablet of rifampicin 450 mg “X” marketed in Indonesia. Methods: Bioequivalence test was analysed using HPLC equipped with UV-Vis detector at 377 nm. The mobile phase used was acetonitrile-phosphate buffer pH 6.8 (45:55) delivered at a flow rate of 1.5 ml/min. Bioequivalence test was conducted on a limited number of subjects (n=8). The subjects were divided into two groups randomly. The pharmacokinetic profiles of the test tablet and reference tablet were statistically calculated using SPSS program to see the test tablet and reference tablet were bioequivalence or not. Results: The developed HPLC method for rifampicin analysis in plasma was sufficiently valid based on the International Conference on Harmonization (ICH) and European Medicines Agency (EMA) guideline, with precision and accuracy values were % Relative Standard Deviation (% RSD = 1.40–13.04) and % Recovery (86.24–102.13), respectively. Meanwhile, the method was linear over studied concentration (0.05 to 10.26 µg/ml) with a coefficient of determination (R2) = 0.9984. The method also had good stability and sensitivity. The result of statistical calculation showed that the generic rifampicin tablet X was bioequivalence toward the reference tablet Rimactan 450 mg. Conclusion: The test rifampicin tablet that was, the generic tablet “X” was bioequivalence toward the reference rifampicin tablet “Rimactan”.